COUNTERACTION TO ILLEGAL MIGRATION IN THE ACTIVITIES OF THE UKRAINE’S STATE BORDER SERVICE - Mota, Andrii (Administrative and Criminal Justice, 2019)
The article is devoted to the scientific review of counteraction to illegal migration by the State Border Service of Ukraine. The features of the theoretical aspects of illegal migration are analyzed. The statistics of activity of border units concerning counteraction to illegal migration are given. The results of the survey of questioned servicemen and employees of the State Border Service of Ukraine regarding the perception of countering illegal migration at the state border and within the controlled border areas are used. The typology of legal ambushes of the state border security agencies was determined. The components of the activity of the State Border Service of Ukraine to counter illegal migration include: preventing illegal migration, fighting it, and protecting the rights of illegal migrants.